2009
DOI: 10.1002/lary.20199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of comorbidity on post‐treatment quality of life scores in patients with head and neck squamous cell carcinoma

Abstract: These data suggest that patient perception of disability, rather than the extent and severity of disease, influences the majority of head and neck disease-specific QOL indices. Analysis of the effects of comorbidity on post-treatment QOL is limited by increased mortality in patients with advanced comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, Gourin et al . [18] concluded that co-morbidity alone did not appear to affect 1-year post-treatment head and neck disease-specific QOL indices in their study and Ronis et al . [19] also reported that head and neck disease-specific domains were less affected by co-morbid illness.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, Gourin et al . [18] concluded that co-morbidity alone did not appear to affect 1-year post-treatment head and neck disease-specific QOL indices in their study and Ronis et al . [19] also reported that head and neck disease-specific domains were less affected by co-morbid illness.…”
Section: Discussionmentioning
confidence: 83%
“…18 This is particularly important as QOL measurements are closely linked to patients' emotional status: in one study lower T and N stage were actually associated with poorer QOL as assessed by questionnaire. 19 It therefore follows that patients' perceptions of their illness may affect QOL as much as or even more than the physiological and anatomical extent of their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid conditions (specifically those associated with psychological well‐being) can easily be considered risk factors for worsened sleep 32. The association between increased mortality and comorbidity in head and neck cancer has been proven, although data establishing the relationship between increased comorbidity and poor quality of life has been conflicting 33, 34. The presence of significant comorbidities among head and neck cancer patients, and their significant impact on symptoms including sleep quality, suggest the need to consider a multidisciplinary approach to patients ensuring that all aspects of care are addressed, rather than focusing attention solely on extirpation of their neoplasm.…”
Section: Discussionmentioning
confidence: 99%